Dynamically adjusted coated glass, and preparation method and detection method thereof
By introducing a self-powered dimming glass system into the coated glass, the visible light transmittance of the coated glass is dynamically adjusted by using the combination of liquid crystal dimming film and photovoltaic components, the problem that existing passive energy-saving glass cannot be dynamically adjusted is solved, and more flexible and efficient energy-saving effects are achieved.
Patent Information
- Application Number
- CN202510132558.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-01
- Publication Date
- 2025-04-29
AI Technical Summary
The existing coated glass is passive energy-saving glass. After installation, the energy-saving effect is fixed and cannot be adjusted dynamically, which limits its application in scenarios where energy-saving effect needs to be flexibly adjusted.
A dynamically adjusted coated glass is designed, adopting the structure of coated glass, hollow layer and dimming layer. A self-powered dimming glass system is provided in the hollow layer, including a liquid crystal dimming film and photovoltaic module. The liquid crystal dimming film is powered by the photovoltaic module to realize the self-power of the liquid crystal dimming film, and the visible light transmittance of the glass is actively adjusted through the directional arrangement of the liquid crystal dimming film.
It realizes the diversified adjustment of the visible light transmittance of glass, and the heat transfer coefficient can be reduced to 0.3-0.5 W/(m2·K), providing a more flexible and efficient energy-saving solution, suitable for the construction and home fields, improving the comfort and health of the living environment.
Smart Images

Figure CN119898088A_ABST
Abstract
Description
[0001] This application is a divisional application. The application number of the original application is 2024103887716, the application date is April 1, 2024, and the name of the invention is "A self-powered dimming energy-saving hollow glass and its preparation method." Technical Field
[0002] The invention relates to the technical field of glass, in particular to a dynamically adjusted coated glass, and a preparation method and a detection method thereof. Background Art
[0003] Glass is an amorphous inorganic non-metallic material. It is generally made of a variety of inorganic minerals as the main raw materials, with a small amount of auxiliary raw materials added. Its main components are silicon dioxide and other oxides. Glass is widely used in buildings. It not only provides a transparent view, but also effectively isolates wind and light, providing the building with good sealing and lighting.
[0004] As people's requirements for living environment increase, coated glass is widely used in the fields of construction and home furnishing due to its excellent UV protection and high infrared reflection performance. The main advantage of coated glass is that it can effectively block ultraviolet rays and reduce harm to the human body. At the same time, its high infrared reflection performance can also improve the thermal insulation effect of the building and reduce the energy consumption of equipment such as air conditioners. However, although coated glass performs well in energy saving, it still has certain limitations. Most of the coated glass on the market is passive energy-saving glass, which means that once installed on the wall, its energy-saving effect is fixed and cannot be adjusted dynamically. This limitation limits the application of coated glass in a wider range of scenarios to a certain extent, especially when the energy-saving effect needs to be flexibly adjusted. Therefore, it is necessary to transform the existing glass and develop a dynamically adjusted coated glass that can adjust its energy-saving effect in real time according to changes in the external environment and user needs, thereby providing a more flexible and efficient energy-saving solution. Summary of the invention
[0005] In view of the technical problem that the existing coated glass mentioned above is a passive energy-saving glass, the energy-saving effect is fixed after being installed on the wall and cannot be dynamically adjusted, the technical solution adopted by the present invention to solve the technical problem is: A dynamically adjustable coated glass, comprising coated glass and a hollow layer, wherein a glass substrate, a first transmission layer, an infrared reflection layer, and a second transmission layer are sequentially arranged on a side of the coated glass facing the hollow layer, a dimming layer is arranged on a side of the hollow layer facing away from the glass substrate, and a self-powered dimming glass system is arranged on the dimming layer, wherein the self-powered dimming glass system comprises a liquid crystal dimming film and a photovoltaic module; The first transmission layer includes a first transmission adhesion film layer connected to the glass substrate, and a first transmission barrier layer connected to the first transmission adhesion film layer and the infrared reflection layer respectively; the second transmission layer includes a second transmission adhesion film layer connected to the hollow layer, and a second transmission barrier layer connected to the second transmission adhesion film layer and the infrared reflection layer respectively; The dimming layer includes a first glass located between the hollow layer and the photovoltaic component, a second glass located on the side of the liquid crystal dimming film away from the photovoltaic component, and a connecting layer, wherein the connecting layer includes a first connecting layer arranged between the first glass and the photovoltaic component, a second connecting layer arranged between the liquid crystal dimming film and the photovoltaic component, and a third connecting layer arranged between the second glass and the liquid crystal dimming film.
[0006] Furthermore, in some embodiments of the present invention, the first transmission adhesion film layer is Si3Al x Si3Al2O3 films of N4 films or O-MWNTs grafted with 2-dimethylaminoethyl chloride hydrochloride x N4 film layer; the thickness of the first transmission adhesion film layer is 30-50nm; the second transmission adhesion film layer is Si3Al x N4 film or Si3Al doped with AZO and ZrO2 x N4 film layer, the thickness of the second transmission adhesion film layer is 50-80nm.
[0007] Furthermore, in some embodiments of the present invention, the first transmission barrier layer is a NiCr film layer with a thickness of 3-5 nm, and the second transmission barrier layer is a NiCr film layer or a NiCrAl film layer with a thickness of 3-5 nm.
[0008] Furthermore, in some embodiments of the present invention, the infrared reflection layer is an AgPdAu alloy film layer, and the thickness of the layer is 10-20 nm.
[0009] Furthermore, in some embodiments of the present invention, the hollow layer is provided with a hollow cavity located between the coated glass and the first glass, and a silica aerogel layer located in the hollow cavity, the peripheral side of the hollow cavity is sealed by silicone structural adhesive, and the thickness of the silica aerogel layer is between 1-5 mm.
[0010] Furthermore, in some embodiments of the present invention, the connecting layer is one of a modified EVA film or a PVB film, and its thickness is 0.76-2.24 mm.
[0011] Furthermore, in some embodiments of the present invention, an aluminum frame is also included for sealing the coated glass and the first glass, the aluminum frame is connected to the coated glass and the first glass via butyl rubber, the hollow cavity is located on the aluminum frame, and the thickness of the hollow cavity is 9-22 mm.
[0012] Furthermore, in some embodiments of the present invention, the photovoltaic components are arranged in an overlapping layout, and the photovoltaic components are photovoltaic cells.
[0013] In addition, the present invention also provides a method for preparing dynamically adjustable coated glass, including the dynamically adjustable coated glass as described above, and comprising the following steps: S1, tempering the glass substrate, cleaning it with deionized water in a glass cleaning machine, and then sending it into a pre-pumped magnetron sputtering coating machine to perform plasma bombardment on the cleaned glass substrate; S2, prepare the first transmission layer. On the basis of the glass substrate, fill the coating chamber with Ar and N2, and adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is SiAl target or SiAl target containing O-MWNTs grafted with 2-dimethylaminoethyl chloride hydrochloride, the sputtering power is 150-300W, and the first transmission adhesion film layer with a film thickness of 30-50nm is formed; on the basis of the first transmission adhesion film layer, Ar is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is NiCr target, the sputtering power is 10-20W, and the first transmission barrier layer with a film thickness of 3-5nm is formed. The first transmission layer is prepared; S3, prepare the infrared reflection layer. On the basis of the first transmission layer, fill Ar in the coating chamber and adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is AgPdAu target, the sputtering power is 150-300W, and the infrared reflection layer with a film thickness of 30-50nm is formed. The infrared reflection layer is prepared; S4, prepare the second transmission layer. On the basis of the infrared reflection layer, fill the coating chamber with Ar and adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is NiCr target or NiCrAl target, the sputtering power is 10-20W, and the second transmission barrier layer with a film thickness of 3-5nm is formed; on the basis of the second transmission barrier layer, Ar and N2 are filled in the coating chamber, and the sputtering pressure is adjusted to 2-4*10 - 1 Pa, the sputtering source is SiAl target or a mixed target containing AZO target, ZrO2 target, SiAl target, the sputtering power is 150-300W, and the second transmission adhesion film layer with a film thickness of 50-80nm is formed; the second transmission layer is prepared; S5, preparing a dimming layer, connecting the liquid crystal dimming film and the photovoltaic module through a connecting layer, forming a self-powered dimming glass system through a circuit, and then using the connecting layer to connect the first glass and the photovoltaic module, and the liquid crystal dimming film and the second glass respectively; S6, prepare a hollow layer, and use butyl glue to seal the coated glass and the first glass on the aluminum frame to form a hollow cavity. Silica aerogel is filled between the hollow cavities to form a silica aerogel layer; the surrounding side of the hollow cavity is sealed with silicone structural adhesive, and the self-powered dimming energy-saving hollow glass is prepared.
[0014] In addition, the present invention also provides a method for testing dynamically regulated coated glass, including the coated glass prepared by the method for preparing dynamically regulated coated glass as described above, and having the following measurement method: A. Preheat the machine; B. Measurement of glass power-off state; C. In the case of step B, perform visible light transmittance calibration; visible light transmittance measurement; D. In the case of step B, perform visible light reflectance calibration: measure the visible light reflectance of one side; measure the visible light reflectance of the other side; E. When the glass is powered off, calculate the heat transfer coefficient according to steps C and D; F. Measurement of glass power-on status; G. In the case of step F, performing visible light transmittance calibration; visible light transmittance measurement; H. In the case of step F, perform visible light reflectance calibration: measure the visible light reflectance of one side; measure the visible light reflectance of the other side; I. When the glass is powered on, calculate the heat transfer coefficient according to steps G and H.
[0015] The beneficial effects of the present invention are as follows: 1. The hollow layer of the present invention has the functions of sound insulation, heat insulation, anti-condensation and energy consumption reduction. The photovoltaic module is used to power the liquid crystal dimming film, which can realize the self-power supply of the liquid crystal dimming film. At the same time, the directional arrangement of the liquid crystal dimming film can actively adjust the visible light transmittance of the glass, and cooperate with the coated glass to realize the combination of active and passive, and two-way energy saving.
[0016] 2. The preparation method of the present invention is stable and controllable, with a high yield rate. The self-powered dimming energy-saving insulating glass prepared can achieve a visible light transmittance of 0-60% through multi-adjustment, and the heat transfer coefficient can be reduced to 0.3-0.5 W / (m 2 ·K); The self-powered dimming energy-saving insulating glass prepared by the present invention can be widely used in the fields of construction and home furnishing, providing people with a more comfortable and healthy living environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a cross-sectional view of a dynamically adjusted coated glass according to the present invention. DETAILED DESCRIPTION
[0018] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0019] like Figure 1 A dynamically adjustable coated glass shown includes a coated glass 1 and a hollow layer 2. A glass substrate 3, a first transmission layer 4, an infrared reflection layer 5, and a second transmission layer 6 are sequentially arranged on the side of the coated glass 1 facing the hollow layer 2. A dimming layer 7 is arranged on the side of the hollow layer 2 facing away from the glass substrate 3. The dimming layer 7 is provided with a self-powered dimming glass system, and the self-powered dimming glass system includes a liquid crystal dimming film 71 and a photovoltaic module 72. Specifically, the photovoltaic module is a photovoltaic cell.
[0020] Furthermore, as a preferred embodiment of the invention but not a limitation, the hollow layer of the present invention has the functions of sound insulation, heat insulation, anti-condensation and energy consumption reduction. The photovoltaic module is used to power the liquid crystal dimming film, and the liquid crystal dimming film can be self-powered. At the same time, the directional arrangement of the liquid crystal dimming film can actively adjust the visible light transmittance of the glass, and cooperate with the coated glass to achieve a combination of active and passive, and two-way energy saving. The first transmission layer of the present invention can selectively transmit visible light and reduce energy loss, the infrared reflection layer can efficiently reflect infrared rays to reduce heat transfer, and the second transmission layer can further optimize light transmission.
[0021] Further, as a preferred embodiment of the invention but not a limitation, the self-powered dimming energy-saving insulating glass uses a liquid crystal dimming film and a photovoltaic module, combining dimmability and self-powering functions. According to the external light intensity and the indoor temperature, the dimming layer can achieve energy saving by automatically or manually adjusting the transmittance. As part of the dimming layer, the liquid crystal dimming film can change the transparency in response to external stimuli such as current, temperature, etc., and realize the function of dynamic adjustment. Specifically, the liquid crystal dimming film can change its optical state under the action of an external electric field, realize the dynamic regulation of the brightness and transmittance of light, and meet the user's demand for indoor light intensity in different time periods or ambient lighting conditions. Users can dynamically adjust the transmittance of the glass through the liquid crystal dimming film as needed to obtain better comfort and privacy protection. The photovoltaic module can convert light energy into electrical energy, provide the liquid crystal dimming film with a self-powered function, thereby realizing the self-powered dimming capability. Specifically, in the present invention, the use of photovoltaic modules enables the self-powered dimming glass system to be self-powered, without the need for an external power supply, and has an energy-saving effect. The photovoltaic module reduces the dependence on traditional energy and helps to reduce carbon emissions. The present invention combines dimming technology and photovoltaic power generation technology, overcomes the limitations of fixed energy-saving effects and dynamic adjustment capabilities of traditional coated glass, has more flexible and intelligent characteristics, and has broad application prospects in the fields of intelligent buildings and energy conservation.
[0022] Specifically, the photovoltaic module is close to the outdoors, and the liquid crystal dimming film is close to the indoors. The self-powered dimming energy-saving insulating glass can dynamically adjust its energy-saving effect under different environments and lighting conditions. When the sun is sufficient, the photovoltaic module can generate more electricity to provide more power for the liquid crystal dimming film. Users can choose a stronger light intensity indoors, or block the light through the liquid crystal dimming film, thereby making the light intensity indoors lower. The photovoltaic module close to the outdoors will not further block the light passing through the liquid crystal dimming film, and thus will not affect people's demand for light intensity when they are indoors.
[0023] Furthermore, as a preferred embodiment of the invention but not a limitation, the hollow layer is located between the coated glass and the dimming layer, which can provide good sound insulation, heat insulation, anti-condensation and energy consumption reduction effects.
[0024] like Figure 1In the dynamically adjustable coated glass shown, the first transmission layer 4 includes a first transmission adhesion film layer 41 connected to the glass substrate 3, and a first transmission barrier layer 42 connected to the first transmission adhesion film layer 41 and the infrared reflection layer 5 respectively; the second transmission layer 6 includes a second transmission adhesion film layer 62 connected to the hollow layer 2, and a second transmission barrier layer 61 connected to the second transmission adhesion film layer 62 and the infrared reflection layer 5 respectively. Further, as a preferred embodiment of the invention but not a limitation, the first transmission adhesion film layer can enhance the adhesion between the first transmission layer and the glass substrate to ensure the close combination between the two. The first transmission barrier layer can block part of the light of a specific wavelength and only allow the light within a specific range to pass through, thereby achieving preliminary adjustment of the light transmission. At the same time, the first transmission barrier layer is connected to the infrared reflection layer, mainly playing the role of isolation and protection, preventing the infrared reflection layer from directly contacting the first transmission adhesion film layer, and avoiding some substances from penetrating from the first transmission adhesion film layer to the infrared reflection layer to affect its function. The second transmission barrier layer can also block light and reduce direct light transmission, thereby improving the thermal insulation performance of the glass. This layer also plays an isolating and protective role, preventing the material close to the hollow layer from directly contacting the infrared reflective layer and affecting the function of the infrared reflective layer. The second transmission adhesion film layer can enhance the adhesion between the second transmission layer and the hollow layer to ensure the stability and reliability of the entire structure. Self-powered dimming energy-saving insulating glass shows higher flexibility and efficiency in light transmission and blocking. In addition, the close combination and synergy between the various film layers enable the glass to effectively block the transmission of infrared rays while maintaining high light transmittance, thereby improving the thermal insulation performance and energy-saving effect of the building.
[0025] like Figure 1 A dynamically adjustable coated glass is shown, the dimming layer 7 includes a first glass 73 located between the hollow layer 2 and the photovoltaic component 72, a second glass 74 located on the side of the liquid crystal dimming film 71 away from the photovoltaic component 72, and a connecting layer, the connecting layer includes a first connecting layer 701 arranged between the first glass 73 and the photovoltaic component 72, a second connecting layer 702 arranged between the liquid crystal dimming film 71 and the photovoltaic component 72, and a third connecting layer 703 arranged between the second glass 74 and the liquid crystal dimming film 71.
[0026] Specifically, the liquid crystal dimming film can dynamically adjust the degree of light transmission, and realize the transmission or blocking of light by changing the arrangement state of liquid crystal molecules. The first connection layer is arranged between the first glass and the photovoltaic module to enhance the adhesion and connection stability between the two, and prevent the photovoltaic module from falling off or shifting during use. The photovoltaic module can convert light energy into electrical energy to provide the required power for the liquid crystal dimming film. The second connection layer is arranged between the liquid crystal dimming film and the photovoltaic module, and a self-powered dimming glass system is formed through circuit connection, which plays the role of connecting, fixing and conducting the current between the two, ensuring that the liquid crystal dimming film can be effectively regulated after receiving the power generated by the photovoltaic module, and can effectively ensure the close connection and stable operation between the two. The second glass is placed on the side of the liquid crystal dimming film away from the photovoltaic module, which also plays a supporting and protective role. The third connection layer is arranged between the second glass and the liquid crystal dimming film to enhance the adhesion and connection stability between the liquid crystal dimming film and the second glass, and ensure that the electrical connection between the liquid crystal dimming film and the entire system is stable and reliable.
[0027] like Figure 1 A dynamically adjustable coated glass is shown, wherein the hollow layer 2 is provided with a hollow cavity 20 located between the coated glass 1 and the first glass 73, and a silica aerogel layer 21 located in the hollow cavity 20, and the periphery of the hollow cavity 20 is sealed by a silicone structural adhesive.
[0028] Furthermore, as a preferred embodiment of the invention but not a limitation, the hollow layer has good heat insulation and sound insulation properties. When placed in the structure of the coated glass and the dimming layer, it can effectively reduce heat conduction and sound conduction, and improve the comfort inside the building. In addition, by adding a hollow layer to the structure of the coated glass and the dimming layer, the strength and wind pressure resistance of the overall structure can be improved, and the stability of the building object can be enhanced. The hollow layer plays an isolating role between the infrared reflection layer and the dimming layer, which can reduce the transfer of external heat energy, reduce the heat conversion rate inside the building, and help save energy and reduce consumption. At the same time, the hollow layer of the present invention can effectively reduce the dew and condensation formed inside the structure of the coated glass and the dimming layer, prevent the glass surface from blurring, and maintain good transparency. Compared with a single-layer thick glass, the structure using a hollow layer can effectively reduce the self-weight of the glass, reduce the load on the building structure, and improve safety.
[0029] Further, as a preferred embodiment of the invention but not a limitation, the hollow cavity is located between the coated glass and the first glass, and is filled with a silica aerogel layer. Silica aerogel has the characteristics of low density, low thermal conductivity, low light scattering and high porosity, which can reduce the scattering and absorption of light, thereby maintaining a high light transmittance while effectively reducing heat conduction and improving the thermal insulation performance of the glass. The use of the silica aerogel layer also enhances the overall structural performance of the glass, improves its compressive strength and durability. Optionally, in some embodiments, in order to maintain a high light transmittance, the thickness of the hollow cavity is 9-22 mm, and the thickness of the silica aerogel layer is controlled within the range of 1-5 mm, which can ensure that while maintaining good thermal insulation performance, the impact on the transmittance is minimized.
[0030] Specifically, by sealing the surrounding sides of the hollow cavity with silicone structural adhesive, which has good weather resistance, bonding strength and good adaptability to a variety of materials, it can not only effectively protect the internal structure of the hollow layer, ensure that the entire hollow cavity maintains a good sealing state for a long time under various environmental conditions, but also prevent the intrusion of gas and water vapor, ensuring the stability, isolation and service life of the hollow layer.
[0031] like Figure 1 The first transmission adhesion film layer 41 is Si3Al x Si3Al2O3 films or O-MWNTs grafted with DCH x N4 film layer; the thickness of the first transmission adhesion film layer 41 is 30-50nm; the second transmission adhesion film layer 62 is Si3Al x N4 film or Si3Al doped with AZO and ZrO2 x N4 film layer, the thickness of the second transmission adhesion film layer 62 is 50-80nm. Further, the sputtering source is a SiAl target, Si:Al (92-95:8-5, calculated by mass percentage). Further, as a preferred embodiment of the invention but not a limitation, the coating chamber is filled with Ar and N2 30-50:30-50 SCCM. The main function is to provide the necessary atmosphere for the sputtering process. Ar is used as a sputtering gas to sputter target atoms by colliding with the target surface, while N2 reacts with the sputtered Si and Al atoms to form Si3Al x N4 film layer. Adjust the sputtering pressure to 2-4*10 -1Pa helps control the stability of the sputtering process and the growth rate of the film. The sputtering power of 150-300W is used to control the sputtering rate and the deposition rate of the film. Different ratios of Si and Al targets can more effectively utilize the sputtering power and achieve rapid deposition of the film without overheating the sample. The appropriate ratio of Si and Al helps to form a uniform and dense Si3Al x N4 film layer, reduce defects and stress in the film layer, improve the overall performance of the film layer, and prevent the film layer from cracking and peeling. Compared with the use of single element targets, a reasonably designed SiAl alloy target can reduce costs to a certain extent, because alloy targets are usually easier to prepare and process than single element targets, and the conductivity of SiAl alloy targets is better than that of pure silicon targets, which can improve the power utilization rate during the sputtering process, thereby improving the sputtering efficiency. The presence of silicon and aluminum elements helps to improve the hardness and toughness of the film layer, so that the film can resist external force impact to a certain extent, and provide sufficient support and wear resistance. The addition of Al can improve the thermal stability of the material, and the appropriate Al content can improve the adhesion between the film layer and the substrate. Al helps to form a stronger chemical bond between the film layer and the substrate. Si3Al x N4 has excellent mechanical properties, chemical stability and wear resistance, as well as good optical and thermal properties. x N4 can improve the light transmittance and transmittance of glass, and can be used as a protective coating to increase the hardness and durability of the glass surface. Applying it to the first transmission adhesion film layer and the second transmission adhesion film layer can effectively enhance the adhesion between the film layer and the adjacent layer, and improve the stability and reliability of the overall structure. During the sputtering process, the flow rate and pressure of N2 gas have a great influence on the density of the film layer, and the ratio of Si and Al will affect the diffusion and reaction of the gas in the film layer, thereby affecting the density of the film layer. When Si3Al x N4 is too thin to improve the visible light transmittance. x N4 is too thick, which results in the visible light reflection color not showing neutral color. The sputtering source of the present invention is SiAl alloy target. The purpose of adding aluminum is to increase the conductivity and improve the sputtering efficiency. When the proportion of Al is too low, it will lead to weak conductivity, unable to start, and Si cannot be sputtered out. When the proportion of Al is too high, it will affect the visible light transmittance, reflectivity and wear resistance. Therefore, the Si3Al x N4 can improve visible light transmittance and increase film adhesion. Optionally, the film can also be made of other high refractive index films, such as TiO2, ZnSnO X wait.
[0032] Further, as a preferred embodiment of the invention but not limiting, Si3Al x N4 film layer and TiO2, ZnSnO XCompared with Si3Al, it has better machining performance. x The N4 film has excellent optical and mechanical properties. By adjusting the ratio of Si and Al, the required transmittance and reflectivity can be obtained. It is suitable for high-end applications such as Low-E glass. x N4, from the cost considerations, the first transmission adhesion film layer is made of Si3Al x N4 is better. Specifically, the preparation cost of TiO2 material is relatively high, and the preparation conditions required for production are more stringent. X Not as good as Si3Al in terms of conductivity and stability in high humidity environments x N4, while in high temperature or humid application scenarios, ZnSnO X Phase changes or decomposition may occur, resulting in performance degradation or failure.
[0033] The present invention helps to form a denser film layer by increasing the nitrogen flow rate, avoids brittleness, reduces defects, and improves transparency. Controlling the sputtering power and reducing the pressure can reduce the internal stress of the film layer, which helps to reduce brittleness. Optionally, after the preparation of the first transmission adhesion film layer or the second transmission adhesion film layer is completed, the film layer can be annealed to release the internal stress and improve the toughness and light transmittance of the film layer.
[0034] In addition, the thickness of the second transmissive adhesion film layer is greater than the thickness of the first transmissive adhesion film layer. The thinner thickness of the first transmissive adhesion film layer is to minimize the scattering and reflection of light while ensuring the adhesion performance, ensuring that the light passes through the glass as much as possible without being absorbed or scattered, thereby improving the transmission performance. As the multi-layer film structure is constructed, each layer needs to be closely combined with the previous layer to ensure the stability of the entire structure. The thicker second transmissive adhesion film layer can provide stronger bonding force, help maintain the integrity of the multi-layer film structure, increase adhesion and improve the durability of the film layer to cope with the influence of external environment and usage conditions.
[0035] Additionally, in some embodiments, Si3Al2O3O-MWNTs grafted with DCH x The N4 film layer can neutralize the surface charge and improve the conductivity of the film layer, thereby enhancing its antistatic ability. The O-MWNTs grafted with DCH can produce interface compatibility, and DCH improves the connection stability between MWNTs and other media, thereby improving the O / N selectivity and permeability of the film layer. In addition, the addition of carbon nanotubes can also improve the thermal stability and mechanical strength of the film layer.
[0036] Specifically, multi-walled carbon nanotubes are reacted with nitric acid to introduce carboxyl oxygen-containing functional groups on the surface of carbon nanotubes, DCH is chemically reacted with activated O-MWNTs through an amidation reaction, the reaction product is washed to remove unreacted impurities and by-products, and then dried. The dried O-MWNTs grafted with DCH are mixed with SiAl powder in a certain proportion, and ultrasonic vibration is used to promote the dispersion of the powder to improve the uniformity of the mixing.
[0037] Specifically, the nitric acid is concentrated nitric acid with a mass fraction of more than 65%, the volume ratio of MWNTs to nitric acid is 1:3 to 1:5, the reaction temperature is controlled at room temperature to 60°C, the time is about 2 hours to 24 hours, and then washed with deionized water to neutrality and dried to obtain O-MWNTs.
[0038] A certain amount of O-MWNTs is dissolved or dispersed in an organic solvent DMF, and an appropriate amount of DCH and catalysts EDC and NHS are added. The molar ratio of the reactants is that the molar ratio of DCH to carboxyl is greater than 1 to ensure sufficient reaction. Specifically, 1 to 5 moles of DCH are required for each mole of O-MWNTs. Specifically, the molar ratio of EDC to O-MWNTs is 1:1 to 5:1. The amount of NHS added is about half of EDC. An appropriate amount of dehydrating agent (such as potassium carbonate, triethylamine, etc.) is added to promote the reaction. The reaction is carried out at room temperature for 2 hours. After the reaction is completed, the product is washed several times with deionized water and organic solvents ethanol or acetone to remove unreacted impurities such as DCH, EDC, and NHS. After washing, it is dried in a vacuum or oven to obtain O-MWNTs grafted with DCH.
[0039] Fill the coating chamber with Ar and N2, and adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is a SiAl target containing O-MWNTs grafted with DCH, the sputtering power is 150-300 W, and the first transmission adhesion film layer with a film thickness of 30-50 nm is formed. In this process, the mixture of chemical reaction products and SiAl is evenly sputtered onto the glass substrate to form a film layer with improved performance.
[0040] Specifically, in some embodiments, the grafting reaction product of DCH and O-MWNTs is not easy to directly participate in the sputtering process, because sputtering is mainly suitable for the deposition of inorganic materials. For materials containing a large amount of organic components, the organic components may be decomposed or destroyed due to high temperature or ion bombardment. As described above, DCH is first successfully grafted onto O-MWNTs by chemical methods, and then the modified O-MWNTs are dispersed in solvent ethanol or isopropanol to form a stable dispersion. In the preparation of Si3Al x In the process of N4 film layer, spin coating can be used to deposit Si3Al xBefore and after the N4 film, the solution containing DCH grafted O-MWNTs was coated on the pretreated Si3Al x On the N4 film, the solution is spread evenly by high-speed rotation and then dried, leaving a layer of evenly distributed nanotube network, making it part of the film structure.
[0041] Specifically, O-MWNTs (oxidized multi-walled carbon nanotubes) are inherently conductive, and when they are grafted with DCH (2-dimethylaminoethyl chloride hydrochloride), the antistatic properties can be further enhanced through the quaternary ammonium groups in the molecular structure of DCH. The quaternary ammonium groups can provide additional surface charges, which help neutralize the static charges accumulated on the surface. x In the layer between the N4 film and the NiCr film, a charge dispersion network can be formed, which helps to quickly disperse and leak the static charge accumulated on the surface, thereby reducing the accumulation of static electricity. - Al x The interface between the N4 film and the NiCr film enhances the adhesion between the layers and may provide a certain charge conduction path, which helps to dissipate static electricity. Due to the introduction of O-MWNTs, the entire glass structure will have better antistatic properties. This is because O-MWNTs can act as a conductive bridge to reduce static electricity accumulation, thereby reducing the impact of static electricity on the glass surface.
[0042] By introducing AZO and ZrO2, stronger chemical bonds can be formed between the film layers, thereby improving the adhesion between the film layers and reducing the risk of film layer shedding. x N4 are all materials with good chemical stability. Their combination may further improve the resistance of the film to chemical corrosion and extend the service life of the film. AZO has good electrical conductivity. Adding AZO can further improve the conductivity of the film, help to better neutralize the surface charge, and thus improve the antistatic ability. At the same time, AZO is a transparent conductive material with better electrical conductivity than the traditional ITO (indium tin oxide) film, and can be used as a more economical and efficient alternative material. The resistivity of the AZO film is low, which helps to improve electron mobility and reduce energy consumption. After adding, it can enhance the transparency of the film, help to improve the transmittance and reduce reflection, thereby improving the optical properties of the transmission adhesion film, which is particularly important for the application of the present invention that requires high light transmittance. ZrO2 has high hardness and wear resistance. Adding ZrO2 can improve the wear resistance and mechanical strength of the film, and enhance its durability and stability in practical applications. ZrO2 is also a barrier material, which can effectively block the diffusion of harmful substances such as sodium ions. In addition, zirconium oxide has the characteristics of high refractive index and low dispersion properties. In Si3Alx Adding ZrO2 to the N4 film can improve the refractive index of the film, and AZO may also provide a certain degree of flexibility to the film, making it better able to resist deformation and damage when subjected to external forces. Zirconia film has good stability at high temperatures and can improve the thermal stability of the composite film, making it suitable for applications in high temperature environments or long-term exposure to sunlight. AZO film can improve the weather resistance of the film and reduce the impact of environmental factors on the performance of the film.
[0043] Specifically, multiple target materials such as SiAl, AZO and ZrO2 are prepared in the sputtering chamber. During the sputtering process, parameters such as sputtering power, sputtering time, atmosphere and pressure need to be precisely controlled. The adjustment of these parameters will affect the deposition rate and proportion of various materials, thereby affecting the composition and performance of the final composite film layer. In the mixed sputtering process, SiAl, AZO and ZrO2 target materials are sputtered simultaneously and mixed and deposited on the substrate surface. By controlling the sputtering power and time of various materials, the content and distribution of various components in the composite film layer can be adjusted. Specifically, Si3Al x The ratio of N4, AZO and ZrO2 is 2:1:1. In the mixed sputtering process, the sputtering time needs to be controlled to achieve the desired film thickness. Specifically, the film thickness can be controlled by monitoring the sputtering rate and the deposition rate.
[0044] like Figure 1 A dynamically adjustable coated glass is shown, wherein the first transmission barrier layer 42 is a NiCr film layer, and its thickness is 3-5nm, and the second transmission barrier layer 61 is a NiCr film layer or a NiCrAl film layer, and its thickness is 3-5nm. Ni:Cr (60-70:40-30, calculated by mass percentage), specifically, the transmission barrier layer can adjust the transmittance and reflectivity of light passing through the insulating glass, thereby realizing the transmission control and energy regulation of light, and then achieving the effect of dimming and energy saving, and the NiCr film layer has good corrosion resistance, high temperature stability and electrical properties. The NiCr film layer is used for the transmission barrier layer, which can adjust the transmittance and reflectivity. At the same time, the NiCr film layer also has high hardness and wear resistance, which can enhance the scratch resistance and service life of the glass. Further, as a preferred embodiment of the invention but not a limitation, doping with an appropriate amount of Cr element can reduce the defects and stress of the NiCr film, thereby improving the overall quality and reliability of the film. The sputtering source is a NiCr alloy target. The corrosion resistance of NiCr alloy film is better than that of pure Ni or pure Cr film, which helps to improve the stability and durability of the film in harsh environments. Specifically, the NiCr film has a high absorption rate. If it is too thick, the film will absorb seriously and the transmittance will drop sharply. If it is too thin, the film cannot be formed. The NiCr film can prevent Na +React with Ag, because sodium exists in the glass substrate, especially in alkaline glass. Long-term exposure to the environment may cause sodium ions to migrate to the surface and contact the silver layer. The chemical reaction between Na and Ag mainly occurs in a humid environment, especially when silver encounters alkali metals, soluble silver salts may be formed. Silver will react with sodium hydroxide seeping from the glass and oxygen in the air to generate opaque silver oxide and sodium nitrate, which will cause the infrared reflection layer to fail and reduce the optical performance and service life of the glass. By setting a corrosion-resistant and stable NiCr film layer between the glass and the silver reflection layer, it can effectively prevent sodium ions from directly contacting silver, thereby avoiding the occurrence of this adverse reaction and ensuring the long-term stability and functionality of the coated glass.
[0045] Due to the change in alloy composition, NiCrAl film provides better spectral selectivity in specific bands. For example, NiCrAl film has better blocking effect in the infrared region, which is beneficial to improve the thermal insulation performance of glass. Compared with pure NiCr, alloyed NiCrAl film may have better corrosion resistance, especially in humid or harsh environments.
[0046] Compared with pure NiCr, the NiCrAl film has better oxidation resistance due to the addition of aluminum, and can more effectively resist the influence of oxidation, corrosion and high temperature environment. The addition of aluminum can improve the adhesion between the film and the substrate, making the NiCrAl film more firmly attached to the film, improving the stability and durability of the film.
[0047] The NiCr film has good conductivity and can reduce charge accumulation. The absorption rate of the NiCr film has a certain upper limit, and as the film becomes thicker, the transmittance decreases. The NiCrAl film has a higher absorption rate. At the same thickness, the NiCrAl film allows less light to pass through, so its transmittance will be lower than that of the NiCr film. If the first transmission blocking layer and the second transmission blocking layer both use the NiCrAl film, most of the light can be blocked, but the subsequent operation endurance of the liquid crystal dimming layer and the photovoltaic module may be insufficient.
[0048] like Figure 1A dynamically adjustable coated glass is shown, wherein the infrared reflection layer 5 is an AgPdAu alloy film layer, and its thickness is 10-20nm. It has excellent infrared reflection performance. The sputtering source is an AgPdAu target, AgPdAu (95-98: 2-1: 3-1, calculated by mass percentage). Further, as a preferred embodiment of the invention but not a limitation, the AgPdAu alloy film layer has a high transmittance in the visible light range and a high reflectivity in the infrared light range. Therefore, it can be used as an infrared reflection layer to control the transmission of light and the regulation of energy. By adding an AgPdAu alloy film layer to the insulating glass, the reflection of infrared light can be achieved and the energy of the light passing through the glass can be reduced. This design can control the temperature difference between indoor and outdoor to a certain extent, improve the thermal insulation performance of the glass, and thus save energy.
[0049] Further, as a preferred embodiment of the invention but not limited thereto, AgPdAu alloy is a high-performance reflective material that combines the high reflectivity of silver, the stability of palladium and the durability of gold. The AgPdAu alloy film layer has excellent reflective properties in the infrared band, can effectively reflect infrared light, and reduce heat transfer through the glass. At the same time, the thickness of the infrared reflective layer is controlled within the range of 10-20nm in order to minimize the impact on light transmission while ensuring the reflection effect. Such a thickness design can not only maintain the high light transmittance of the glass, but also achieve effective infrared reflection and improve the thermal insulation performance of the glass. Specifically, Ag, as the main component, can significantly improve the reflective effect of the film layer on infrared rays, thereby playing a good heat insulation role and reducing heat transmission. The addition of palladium (Pd) and gold (Au) helps to improve the corrosion resistance and oxidation resistance of the alloy film layer. Pd has a good anti-sulfurization ability, while Au has extremely high chemical stability. Their combined effect makes the alloy film layer more stable under various environmental conditions and prolongs its service life. Metals with high refractive indexes, such as Ag, can increase the light-capturing ability of the film, while metals with low refractive indexes, such as Au, may make the film more transparent to light. In addition, a small amount of Au and Pd can help adjust the transmission characteristics of the film in the visible light region and improve the hardness and toughness of the film to a certain extent, so that the coated glass can maintain good heat insulation while also ensuring good light transmittance.
[0050] Since the melting point of AgPdAu alloy is low, it is easier to form a uniform and dense film during the preparation process, and the sputtering efficiency is high. At the same time, the appropriate ratio of Pd and Au can also prevent the pure Ag film from oxidizing and discoloring in high temperature or humid environment.
[0051] Furthermore, as a preferred embodiment of the invention but not a limitation, the AgPdAu alloy film layer can reduce and improve the infrared blocking ability. Compared with the Ag film, the corrosion resistance and wear resistance of the AgPdAu alloy film layer are significantly improved. If the AgPdAu alloy film layer is too thick, the visible light transmittance is too low and the reflectivity is too high; if it is too thin, the emissivity becomes large and the low-radiation effect cannot be achieved. The AgPdAu alloy film layer can effectively reflect most of the infrared part of solar radiation while ensuring good adhesion and mechanical strength, thereby reducing the heat transferred to indoor or outdoor through the glass, achieving a significant thermal insulation effect. At this thickness of the present invention, the emissivity of the film layer is about 0.02. The sputtering source is an AgPdAu alloy target, which can improve the performance of subsequent processing, such as the need for transportation and cleaning during hollowing. Specifically, although the film layer is thin, the AgPdAu alloy film layer is uniform and dense, with moderate hardness, not too soft nor brittle, and not easily damaged by slight collisions or scratches during transportation, ensuring the integrity of the coated glass during the transition from the coating link to the next step such as hollowing in the production process. Ag, Pd, and Au are all metal elements with strong corrosion resistance, and the alloy film layer formed also has high resistance to chemical erosion. During the cleaning process, it can better resist the damage of the cleaning agent to the film layer, and maintain the stability of the film layer structure and performance.
[0052] like Figure 1 In the dynamically adjustable coated glass shown, the connecting layer is one of a modified EVA film or a PVB film, and its thickness is 0.76-2.24 mm. Further, as a preferred embodiment of the invention but not a limitation, the main function of the connecting layer is to firmly bond the two glass plates of the insulating glass together to form a sealed space. This can prevent foreign substances such as moisture and dust from entering the insulating glass, while also providing a certain structural strength.
[0053] EVA film ethylene vinyl acetate copolymer and PVB film polyvinyl acetate both have good adhesion, flexibility and UV resistance, and can effectively bond all layers of insulating glass. As bonding and isolation media in the middle of laminated glass, EVA film and PVB film have excellent transparency, weather resistance and bonding strength. The connecting layer with a thickness of 0.76-2.24mm can provide sufficient structural support and adhesion to ensure the stability and sealing performance of insulating glass. The transmittance of EVA film is greater than 90%, while the transmittance of PVB film is about 85-90%. However, ordinary EVA film is easy to soften at high temperature, resulting in a decrease in connection performance and is not suitable for applications in high temperature environments. At the same time, ordinary EVA film is sensitive to ultraviolet rays and is easily affected by ultraviolet rays and aging and deterioration. Relatively speaking, PVB film has better heat and weather resistance, and can also play a certain role in sound insulation and heat insulation, improving the comprehensive performance of glass.
[0054] Specifically, calculated by mass percentage, the production steps of modified EVA are as follows: Step 1: Mix 60% EVA resin and 10% polymethyl methacrylate, add 0.1% coupling agent dilauryl titanate and 5% compatibilizer acrylate-methacrylate copolymer, and stir well. The transmittance of polymethyl methacrylate is about 92%, and it has excellent weather resistance and transparency. The coupling agent dilauryl titanate and the compatibilizer acrylate-methacrylate copolymer help to improve the compatibility of EVA and polymethyl methacrylate. The acrylate-methacrylate copolymer has good compatibility with polymethyl methacrylate and interacts with EVA through hydrogen bonds or van der Waals forces, thereby obtaining a more stable blending system.
[0055] Step 2: Add 1% zinc oxide nanoparticles and 0.2% indium tin oxide nanoparticles to the mixed system. Zinc oxide nanoparticles and indium tin oxide nanoparticles have high transparency and can significantly improve the conductive properties of the blend. These fillers form a conductive network in the EVA / polymethyl methacrylate matrix, allowing the connecting layer to effectively transmit electrical signals.
[0056] Step 3: Mix the inorganic fillers 1% montmorillonite and 0.5% wollastonite with coupling agent KH-550 and add them to the mixed system. Control the dosage to achieve the required mechanical properties and dimensional stability, further enhance the mechanical properties and thermal stability of the blend, and may help improve its barrier properties.
[0057] Step 4: Adding 1% cross-linking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride into the mixed system can increase the cross-linking density of the blend and enhance the mechanical properties and heat resistance of the material.
[0058] Step 5: Adding 1% plasticizers of acetyl tributyl citrate and triphenyl phosphate into the mixed system can improve the processing performance and flexibility of the blend. Triphenyl phosphate and acetyl tributyl citrate have high light transmittance while maintaining the stability of other physical properties.
[0059] Step 6: Adding the ultraviolet absorber 2,2'-methylenebis[4-(2-hydroxy-3-tert-butylphenoxy)phenylpropionic acid] and the antioxidant N,N'-di(1,4-cyclohexyl)-N,N'-diphenyl-p-phenylenediamine into the mixed system can effectively improve the weather resistance and aging resistance of the EVA / polymethyl methacrylate blend and extend the service life of the connecting layer.
[0060] Step 7: Melt blending the mixed system, which can be done using a twin-screw extruder or other suitable equipment. During the blending process, the temperature, pressure and screw speed need to be controlled to ensure that the components are fully dispersed and mixed.
[0061] Step 8: Cool and pelletize the blended material to obtain an improved EVA connecting layer material.
[0062] By introducing modified EVA film, the light transmittance is higher than that of PVB film, which will not affect the performance of photovoltaic modules. In addition, the modified EVA has good mechanical properties and conductive effects, and can be used for connection in photovoltaic modules for a long time without aging and loosening.
[0063] Specifically, there are multiple photovoltaic cells in the photovoltaic module. In traditional photovoltaic modules, the cells are usually arranged at a certain interval and connected together by welding strips or conductive adhesives. In this way, there will be gaps between the cells, resulting in some light not being effectively utilized. The photovoltaic module of the present invention adopts an overlapping layout. The cells are arranged closely like tiles on the roof, one piece covers the previous piece, but only covers the unilluminated part below it, thereby eliminating the physical spacing between the cells. The present invention cuts the cells into smaller units and then arranges them in an overlapping manner at a certain angle, such as 1-2 degrees, so that adjacent small cells overlap partially. Due to the overlap between the small cells, there is no cell spacing, which greatly reduces the overall gap area of the module and increases the light-receiving area. The light-receiving area of the overlapping cells can reach more than 90%, which is about 10% higher than the light-receiving area of the traditional module. Due to the increase in the light-receiving area, the power output of the overlapping cells is also increased accordingly. Overlapping cells can achieve longer battery strings, thereby obtaining larger module size and power output with the same number of cells. The efficiency of overlapping cells can reach more than 20%, and the power gain can reach 11%-13% compared to traditional modules.
[0064] like Figure 1The dynamically adjusted coated glass shown in the figure also includes an aluminum frame 8 for sealing the coated glass 1 and the first glass 73, the aluminum frame 8 is connected to the coated glass 1 and the first glass 73 by butyl rubber, the hollow cavity 20 is located on the aluminum frame 8, and the thickness of the hollow cavity 20 is 9-22 mm. Specifically, the aluminum frame plays a supporting and sealing role in the hollow glass structure. It can ensure that the connection between the coated glass and the first glass is tight and reliable, and can also provide good support and positioning for the hollow cavity. Butyl rubber, as a high-performance sealing material, has excellent water resistance, air resistance and aging resistance, can effectively fill the gap between the aluminum frame and the coated glass and the first glass, and form a solid sealing barrier to prevent external moisture, air, dust and other impurities from entering the hollow cavity. By using butyl rubber sealing, air and moisture can be effectively prevented from entering the hollow cavity while maintaining the stability of the structure. The thickness of the hollow cavity of the present invention can ensure a good thermal insulation effect while avoiding the structure being too bulky or too weak. In addition, the existence of the hollow cavity also forms an air barrier, which further enhances the thermal insulation performance of the insulating glass, can effectively reduce heat transfer and improve sound insulation performance, while also meeting the needs of thermal insulation, sound insulation and other performance in different application scenarios.
[0065] A method for preparing dynamically adjusted coated glass comprises the following steps: S1, tempering the glass substrate 3, cleaning it with deionized water in a glass cleaning machine, and then sending it into a pre-pumped magnetron sputtering coating machine to perform plasma bombardment on the cleaned glass substrate 3; Specifically, the 4-8mm high-quality glass substrate is tempered. After the tempered glass is heated to 600-620 degrees and softened for 3-5 minutes, it is quenched by blowing for 2-5 minutes. After the glass is cleaned with deionized water in a glass cleaning machine, it is sent to a pre-evacuated magnetron sputtering coating machine. Its base vacuum is 5*10 -4 Pa. Plasma bombardment is performed on the cleaned tempered glass, 1-2KW, 3-5min. Tempering is a processing technology that improves the strength and impact resistance of glass. By heating the glass to the softening temperature of 600-620 degrees, and then quickly blowing air to quench it, the glass surface is quickly cooled, and compressive stress is generated inside, thereby increasing the bending resistance and impact resistance of the glass, and improving the strength and safety of the glass. Once the tempered glass is broken, it will break into small particles, reducing the harm to the human body. Plasma bombardment is to clean the glass surface and remove gases, making it more suitable for subsequent thin film coating, ensuring the adhesion and quality of the film, and improving the optical properties.
[0066] S2, prepare the first transmission layer 4, on the basis of the glass substrate 3, fill Ar and N2 into the coating chamber, adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is SiAl target or SiAl target of O-MWNTs grafted with DCH, the sputtering power is 150-300W, and the first transmission adhesion film layer 41 with a film thickness of 30-50nm is formed; on the basis of the first transmission adhesion film layer 41, Ar is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is NiCr target, the sputtering power is 10-20W, and the first transmission barrier layer 42 with a film thickness of 3-5nm is formed. The first transmission layer 4 is prepared; Specifically, Si3Al x N4 film layer, film thickness 30-50nm. Ar and N2 (30-50:30-50SCCM) are filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92-95:8-5, calculated by mass percentage), the sputtering power is 150-300W, and the sputtering time is adjusted to make the film thickness 30-50nm.
[0067] Specifically, Si3Al2O3O2-grafted DCH O-MWNTs x N4 film layer, film thickness 30-50nm. Ar and N2 (30-50:30-50SCCM) are filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is a SiAl target of O-MWNTs grafted with DCH, Si:Al (92-95:8-5, calculated by mass percentage), the sputtering power is 150-300W, and the sputtering time is adjusted to make the film thickness 30-50nm.
[0068] Alternatively, Si3Al x The solution containing DCH grafted O-MWNTs was coated on the pretreated Si3Al x On the N4 film, the solution is spread evenly by high-speed rotation and then dried, leaving a layer of evenly distributed nanotube network, making it part of the film structure.
[0069] Specifically, the thickness of the NiCr film layer is 3-5 nm. Ar (30-50 SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is NiCr target, Ni:Cr (60-70:40-30, calculated by mass percentage), the sputtering power is 10-20W, and the sputtering time is adjusted to make the film thickness 3-5nm.
[0070] S3, prepare the infrared reflection layer 5, fill Ar in the coating chamber on the basis of the first transmission layer 4, and adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is AgPdAu target, the sputtering power is 150-300W, and the infrared reflection layer 5 with a film thickness of 30-50nm is formed. The infrared reflection layer 5 is prepared; the thickness of the AgPdAu alloy film is 10-20nm. Specifically, Ar (30-50SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is AgPdAu target, AgPdAu (95-98: 2-1: 13-1, calculated by mass percentage), the sputtering power is 150-300W, and the sputtering time is adjusted to make the film thickness 30-50nm. By adjusting the deposition effect of the alloy film layer, the surface roughness of the alloy film layer can be changed, thereby affecting its optical properties.
[0071] S4, prepare the second transmission layer 6, on the basis of the infrared reflection layer 5, fill the coating chamber with Ar, adjust the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is NiCr target or NiCrAl target, the sputtering power is 10-20W, and the second transmission barrier layer 61 with a film thickness of 3-5nm is formed; on the basis of the second transmission barrier layer 61, Ar and N2 are filled in the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is SiAl target or a mixed target containing AZO target, ZrO2 target, SiAl target, the sputtering power is 150-300W, and the second transmission adhesion film layer 62 with a film thickness of 50-80nm is formed; the second transmission layer 6 is prepared; Specifically, Si3Al x N4 film layer, film thickness 50-80nm. Ar and N2 (30-50:30-50 SCCM) are filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92-95:8-5, calculated by mass percentage), the sputtering power is 150-300W, and the sputtering time is adjusted to make the film thickness 50-80nm.
[0072] Specifically, Si3Al2O3 containing AZO and ZrO2 x N4 film layer, film thickness 50-80nm. Ar and N2 (30-50:30-50 SCCM) are filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is a mixed target containing AZO target, ZrO2 target, and SiAl target, Si:Al (92-95:8-5, calculated by mass percentage), AZO: ZrO2: Si3Al xThe ratio of N4 is 1:1:2, the sputtering power is 150-300W, and the sputtering time is adjusted to make the film thickness 50-80nm.
[0073] Specifically, the thickness of the NiCr film layer is 3-5 nm. Ar (30-50 SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is NiCr target, Ni:Cr (60-70:40-30, calculated by mass percentage), the sputtering power is 10-20W, and the sputtering time is adjusted to make the film thickness 3-5nm.
[0074] Specifically, the thickness of the NiCrAl film is 3-5nm. Ar (30-50 SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is NiCrAl target, Ni:Cr:Al (50-60:30-40:10-20 calculated by mass percentage), the sputtering power is 10-20W, and the sputtering time is adjusted to make the film thickness 3-5nm.
[0075] S5, prepare the dimming layer 7, the connecting layer connects the liquid crystal dimming film 71 and the photovoltaic module 72, forms a self-powered dimming glass system through the circuit, and then uses the connecting layer to connect the first glass 73 and the photovoltaic module 72, and the liquid crystal dimming film 71 and the second glass 74 respectively; the thickness of the connecting layer is 0.76-2.24mm; Specifically, the liquid crystal dimming film can dynamically adjust the degree of light transmission, and realize the transmission or blocking of light by changing the arrangement state of liquid crystal molecules. The first connection layer is arranged between the first glass and the photovoltaic module to enhance the adhesion and connection stability between the two, and prevent the photovoltaic module from falling off or shifting during use. The photovoltaic module is responsible for converting light energy into electrical energy to provide the required power for the liquid crystal dimming film. The second connection layer is arranged between the liquid crystal dimming film and the photovoltaic module, and a self-powered dimming glass system is formed through circuit connection, which plays the role of connecting, fixing and conducting the current between the two, ensuring that the liquid crystal dimming film can be effectively regulated after receiving the power generated by the photovoltaic module, and can effectively ensure the close connection and stable operation between the two. The second glass is placed on the side of the liquid crystal dimming film away from the photovoltaic module, which also plays a supporting and protective role. The third connection layer is arranged between the second glass and the liquid crystal dimming film to enhance the adhesion and connection stability between the liquid crystal dimming film and the second glass, and ensure that the electrical connection between the liquid crystal dimming film and the entire system is stable and reliable.
[0076] S6, prepare the hollow layer 2, the aluminum frame 8 seals the coated glass 1 and the first glass 73 with butyl glue to form a hollow cavity 20, and the middle cavity 20 is filled with silica aerogel to form a silica aerogel layer 21; the hollow cavity 20 is sealed with silicone structural glue, and the self-powered dimming energy-saving hollow glass is prepared. Specifically, the aluminum frame plays a supporting and sealing role in the hollow glass structure. It can ensure that the connection between the coated glass and the first glass is tight and reliable, and can also provide good support and positioning for the hollow cavity. As a high-performance sealing material, butyl glue has excellent water resistance, air resistance and aging resistance, and can effectively fill the gap between the aluminum frame and the coated glass and the first glass to form a solid sealing barrier to prevent external moisture, air, dust and other impurities from entering the hollow cavity. By using butyl glue for sealing, air and moisture can be effectively prevented from entering the hollow cavity while maintaining the stability of the structure. The thickness of the hollow cavity of the present invention can ensure a good thermal insulation effect while avoiding the structure being too bulky or too weak. In addition, the presence of the hollow cavity also forms an air barrier, which further enhances the thermal insulation performance of the hollow glass, can effectively reduce heat transfer, improve sound insulation performance, and also meet the requirements for thermal insulation, sound insulation and other performance in different application scenarios. Silica aerogel has the characteristics of low density, low thermal conductivity and high porosity, which can effectively reduce heat conduction and improve the thermal insulation performance of glass. The application of the silica aerogel layer also enhances the overall structural performance of the glass, improving its compressive strength and durability.
[0077] Specific testing method: Test instrument: Glas Spec2500 Test conditions: 25-35℃, humidity: <50% Measurement wavelength range: 300nm-2500nm Measurement method: 1. Preheat the machine, turn on the machine power, start the Glas Spec2500 application, and preheat for 15-20 minutes; Glass power-off state measurement: turn off the power of the glass; 2. Visible light transmittance calibration: Use the software provided by the program to perform visible 100% and 0 zero point calibration; 3. Visible light transmittance measurement: Put the glass after power off into the measurement window of the calibrated instrument, start the visible light transmittance measurement button, measure the visible light transmittance of 300-2500nm, measure one point every 2nm, and take the integral value as the visible light transmittance value when power off; 4. Visible light reflectance calibration: Do not remove the glass, use the program's built-in software to calibrate the visible light reflectance; 5. Visible light reflectance measurement on one side: Start the visible light reflectance measurement button, measure the visible light transmittance of 300-2500nm on one side, measure one point every 2nm, and take the integral value as the visible light reflectance value of the side when the power is off; 6. Measure the visible light reflectance of the other side: Turn the glass over, start the visible light reflectance measurement button, measure the visible light transmittance of 300-2500nm on the other side, measure a point every 2nm, and take the integral value as the visible light reflectance value of the side when the power is off; 7. Calculation of heat transfer coefficient: According to the measurement results of visible light transmittance and reflectance, press the calculation button to directly calculate the heat transfer coefficient; When the glass is powered off, the visible light transmittance is 0-2% and the heat transfer coefficient is 0.3-0.45W / (m 2 K); Measurement of glass power-on state: Apply 70V voltage to the glass using a DC power supply; 8. Visible light transmittance calibration: Use the software provided by the program to perform visible 100% and 0 zero point calibration; 9. Visible light transmittance measurement: Put the powered-on glass into the calibrated instrument measurement window, start the visible light transmittance measurement button, measure the visible light transmittance of 300-2500nm at a point every 2nm, and take the integral value as the visible light transmittance value when the power is off; 10. Calibration of visible light reflectance: Do not remove the glass, and use the software that comes with the program to calibrate the visible light reflectance; 11. Measurement of visible light reflectance on one side: Start the visible light reflectance measurement button, measure the visible light transmittance of 300-2500nm on one side, measure one point every 2nm, and take the integral value as the visible light reflectance value of the side when power is on; 12. Measurement of visible light reflectance on the other side: Turn the glass over, start the visible light reflectance measurement button, measure the visible light transmittance of 300-2500nm on the other side, measure a point every 2nm, and take the integral value as the visible light reflectance value of the side when power is on; 13. Calculation of heat transfer coefficient: According to the measurement results of visible light transmittance and reflectance, press the calculation button to directly calculate the heat transfer coefficient; When the glass is powered off, the visible light transmittance is 45-65%, and the heat transfer coefficient is 0.34-0.60W / (m 2 ·K).
[0078] Example 1 S1, tempering treatment is performed on 8mm high-quality glass substrate. After tempering treatment, the glass is heated to 620 degrees and softened for 5 minutes, then quenched by blowing for 5 minutes. The glass is cleaned with deionized water in a glass cleaning machine and then sent to a pre-evacuated magnetron sputtering coating machine. The base vacuum is 5*10 -4Pa. Plasma bombardment of cleaned tempered glass, 2KW, 5min.
[0079] S2, prepare the first transmission layer 4, on the basis of the glass substrate 3, fill the coating chamber with Ar and N2 (50:50 SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the first transmission adhesion film layer 41 with a film thickness of 50nm is formed; on the basis of the first transmission adhesion film layer 41, Ar (30SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 4*10 -1 Pa, the sputtering source is NiCr target, the sputtering power is 20W, and the first transmission barrier layer 42 with a film thickness of 5nm is formed. The first transmission layer 4 is prepared; S3, prepare the infrared reflection layer 5, on the basis of the first transmission layer 4, fill the coating chamber with Ar (50SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is AgPdAu target, AgPdAu (95:2:5, calculated by mass percentage), the sputtering power is 300W, and the infrared reflection layer 5 with a film thickness of 50nm is formed. The infrared reflection layer 5 is prepared; S4, prepare the second transmission layer 6, on the basis of the infrared reflection layer 5, fill the coating chamber with Ar (30SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is NiCr target, Ni:Cr (60:40, calculated by mass percentage), the sputtering power is 20W, and the second transmission barrier layer 61 with a film thickness of 5nm is formed; on the basis of the second transmission barrier layer 61, Ar and N2 (50:50 SCCM) are filled in the coating chamber, and the sputtering pressure is adjusted to 4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the second transmission adhesion film layer 62 with a film thickness of 70nm is formed; the second transmission layer 6 is prepared; S5, prepare the dimming layer 7, the connecting layer connects the liquid crystal dimming film 71 and the photovoltaic module 72, and forms a self-powered dimming glass system through the circuit, and then uses the connecting layer to connect the first glass 73 and the photovoltaic module 72, and the liquid crystal dimming film 71 and the second glass 74 respectively. The thickness of the connecting layer is 1.2mm, and the connecting layer is a PVB film. The photovoltaic module adopts an overlapping layout. The photovoltaic module is a photovoltaic cell. The photovoltaic cell is cut into smaller units and then overlapped and arranged at a certain angle of 1-2 degrees, so that adjacent cell pieces partially overlap and are arranged as closely as roof tiles. One piece covers the previous piece, but only covers the unilluminated part below it, thereby eliminating the physical spacing between the cells; The production steps of modified EVA are as follows: Step 1: Mix 60% EVA resin and 10% polymethyl methacrylate, add 0.1% coupling agent dilauryl titanate and 5% compatibilizer acrylate-methacrylate copolymer, and stir well; Step 2: adding 1% zinc oxide nanoparticles and 0.2% indium tin oxide nanoparticles into the mixed system; Step 3: Mix the inorganic filler 1% montmorillonite and 0.5% wollastonite with the coupling agent KH-550 and add them into the mixed system; Step 4: Add 1% cross-linking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride into the mixed system; Step 5: Add 1% plasticizers of acetyl tributyl citrate and triphenyl phosphate into the mixed system; Step 6: adding the ultraviolet absorber 2,2'-methylenebis[4-(2-hydroxy-3-tert-butylphenoxy)phenylpropionic acid] and the antioxidant N,N'-di(1,4-cyclohexyl)-N,N'-diphenyl-p-phenylenediamine to the mixed system; Step 7: Melt blend the mixed system, which can be done by a twin-screw extruder or other suitable equipment. During the blending process, the temperature of each zone may be: 80℃-110℃ in the feeding zone, 120℃-160℃ in the melting zone, 160℃-200℃ in the metering zone, the speed is 50-100 rpm, and the pressure is controlled between 10-30 MPa to ensure that the components are fully dispersed and mixed.
[0080] Step 8: Cool and pelletize the blended material to obtain an improved EVA connecting layer material.
[0081] S6, prepare the hollow layer 2, the aluminum frame 8 seals the coated glass 1 and the first glass 73 with butyl glue to form a hollow cavity 20, the thickness of the hollow cavity 20 is 12 mm, and the middle cavity 20 is filled with silica aerogel to form a silica aerogel layer 21; the thickness of the silica aerogel layer 21 is 2 mm, and the surrounding side of the hollow cavity 20 is sealed with silicone structural glue, and the self-powered dimming energy-saving hollow glass is prepared.
[0082] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0083] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 1 is 52.6%, and the heat transfer coefficient is 0.35 W / (m 2 ·K).
[0084] Example 2 S1, tempering treatment is performed on 6mm high-quality glass substrate. After tempering treatment, the glass is heated to 600 degrees and softened for 4 minutes, then quenched by blowing for 3 minutes. After the glass is cleaned with deionized water in a glass cleaning machine, it is sent to a pre-evacuated magnetron sputtering coating machine. The base vacuum is 5*10 -4 Pa. Plasma bombardment of cleaned tempered glass, 2KW, 3min.
[0085] S2, prepare the first transmission layer 4, on the basis of the glass substrate 3, fill the coating chamber with Ar and N2 (50:50 SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the first transmission adhesion film layer 41 with a film thickness of 30nm is formed; on the basis of the first transmission adhesion film layer 41, Ar (30SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 4*10 -1 Pa, the sputtering source is NiCr target, the sputtering power is 20W, and the first transmission barrier layer 42 with a film thickness of 3nm is formed. The first transmission layer 4 is prepared; S3, preparing the infrared reflection layer 5. On the basis of the first transmission layer 4, Ar (50 SCCM) is filled in the coating chamber, the sputtering pressure is adjusted to 3*10-1Pa, the sputtering source is AgPdAu target, AgPdAu (95:2:5, calculated by mass percentage), the sputtering power is 200W, and the infrared reflection layer 5 with a film thickness of 50nm is formed. The infrared reflection layer 5 is prepared; S4, prepare the second transmission layer 6, on the basis of the infrared reflection layer 5, fill the coating chamber with Ar (30SCCM), adjust the sputtering pressure to 3*10 -1Pa, the sputtering source is NiCr target, Ni:Cr (60:40, calculated by mass percentage), the sputtering power is 20W, and the second transmission barrier layer 61 with a film thickness of 3nm is formed; on the basis of the second transmission barrier layer 61, Ar and N2 (50:50 SCCM) are filled in the coating chamber, and the sputtering pressure is adjusted to 3*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the second transmission adhesion film layer 62 with a film thickness of 70nm is formed; the second transmission layer 6 is prepared; S5, prepare the dimming layer 7, the connecting layer connects the liquid crystal dimming film 71 and the photovoltaic module 72, and forms a self-powered dimming glass system through the circuit, and then uses the connecting layer to connect the first glass 73 and the photovoltaic module 72, and the liquid crystal dimming film 71 and the second glass 74 respectively. The thickness of the connecting layer is 0.8mm, and the photovoltaic module adopts an overlapping layout. The connecting layer is a PVB film. The photovoltaic module adopts an overlapping layout. The photovoltaic module is a photovoltaic cell. The photovoltaic cell is cut into smaller units and then overlapped at a certain angle of 1-2 degrees to make adjacent cell pieces partially overlap. They are arranged as closely as roof tiles, one piece covers the previous piece, but only covers the unilluminated part below it, thereby eliminating the physical spacing between the cells; S6, prepare the hollow layer 2, and the aluminum frame 8 seals the coated glass 1 and the first glass 73 with butyl glue to form a hollow cavity 20. The thickness of the hollow cavity 20 is 15 mm. Silica aerogel is filled between the middle cavity 20 to form a silica aerogel layer 21; the thickness of the silica aerogel layer 21 is 1 mm, and the surrounding side of the hollow cavity 20 is sealed with silicone structural adhesive. The self-powered dimming energy-saving hollow glass is prepared.
[0086] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.35W / (m 2 ·K).
[0087] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 2 is 53.6%, and the heat transfer coefficient is 0.4 W / (m 2 ·K).
[0088] Example 3 S1, tempering treatment is performed on 8mm high-quality glass substrate. After tempering treatment, the glass is heated to 620 degrees and softened for 5 minutes, then quenched by blowing for 5 minutes. The glass is cleaned with deionized water in a glass cleaning machine and then sent to a pre-evacuated magnetron sputtering coating machine. The base vacuum is 5*10 -4 Pa. Plasma bombardment of cleaned tempered glass, 2KW, 5min.
[0089] S2, prepare the first transmission layer 4, on the basis of the glass substrate 3, fill the coating chamber with Ar and N2 (50:50 SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the first transmission adhesion film layer 41 with a film thickness of 30nm is formed; on the basis of the first transmission adhesion film layer 41, Ar (30SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 4*10 -1 Pa, the sputtering source is NiCr target, the sputtering power is 20W, and the first transmission barrier layer 42 with a film thickness of 3nm is formed. The first transmission layer 4 is prepared; S3, prepare the infrared reflection layer 5, on the basis of the first transmission layer 4, fill the coating chamber with Ar (50SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is AgPdAu target, AgPdAu (95:2:8, calculated by mass percentage), the sputtering power is 300W, and the infrared reflection layer 5 with a film thickness of 30nm is formed. The infrared reflection layer 5 is prepared; S4, prepare the second transmission layer 6, on the basis of the infrared reflection layer 5, fill the coating chamber with Ar (30SCCM), adjust the sputtering pressure to 4*10 -1 Pa, the sputtering source is NiCr target, Ni:Cr (60:40, calculated by mass percentage), the sputtering power is 20W, and the second transmission barrier layer 61 with a film thickness of 3nm is formed; on the basis of the second transmission barrier layer 61, Ar and N2 (50:50 SCCM) are filled in the coating chamber, and the sputtering pressure is adjusted to 4*10 -1 Pa, the sputtering source is SiAl target, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the second transmission adhesion film layer 62 with a film thickness of 50nm is formed; the second transmission layer 6 is prepared; S5, prepare the dimming layer 7, the connecting layer connects the liquid crystal dimming film 71 and the photovoltaic module 72, and forms a self-powered dimming glass system through the circuit, and then uses the connecting layer to connect the first glass 73 and the photovoltaic module 72, and the liquid crystal dimming film 71 and the second glass 74 respectively. The thickness of the connecting layer is 1mm, and the photovoltaic module adopts an overlapping layout. The connecting layer is a PVB film. The photovoltaic module adopts an overlapping layout. The photovoltaic module is a photovoltaic cell. The photovoltaic cell is cut into smaller units and then overlapped at a certain angle of 1-2 degrees to make adjacent cell pieces partially overlap. They are arranged as closely as roof tiles, one piece covers the previous piece, but only covers the unilluminated part below it, thereby eliminating the physical spacing between the cells; S6, prepare the hollow layer 2, the aluminum frame 8 seals the coated glass 1 and the first glass 73 with butyl glue to form a hollow cavity 20, the thickness of the hollow cavity 20 is 9 mm, and the middle cavity 20 is filled with silica aerogel to form a silica aerogel layer 21; the thickness of the silica aerogel layer 21 is 1 mm, and the surrounding side of the hollow cavity 20 is sealed with silicone structural glue, and the self-powered dimming energy-saving hollow glass is prepared.
[0090] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.45W / (m 2 ·K).
[0091] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 3 is 59.7%, and the heat transfer coefficient is 0.49 W / (m 2 ·K).
[0092] Example 4 The difference between Example 4 and Example 1 is that the photovoltaic components are arranged in a matrix with intervals.
[0093] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0094] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 4 is 50.1%, and the heat transfer coefficient is 0.32 W / (m 2 ·K).
[0095] Example 5 The difference between Example 5 and Example 1 is that the thickness of the silica aerogel layer 21 is 6.5 mm.
[0096] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0097] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 5 is 34.3%, and the heat transfer coefficient is 0.31 W / (m 2 ·K).
[0098] Example 6 The difference between Example 6 and Example 1 is that the connection layer adopts PVB film with a thickness of 2.8 mm.
[0099] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0100] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 6 is 36.6%, and the heat transfer coefficient is 0.28 W / (m 2 ·K).
[0101] Example 7 The difference between Example 7 and Example 1 is that the Si3Al2O3O-MWNTs grafted with DCH is prepared. x N4, specifically, the nitric acid is concentrated nitric acid with a mass fraction of more than 65%, the volume ratio of MWNTs to nitric acid is 1:3, the reaction temperature is controlled at 40°C, the time is about 5 hours, and then washed with deionized water to neutrality and dried to obtain O-MWNTs.
[0102] A certain amount of O-MWNTs is dissolved or dispersed in an organic solvent, DMF. 1.05 moles of DCH are required for each mole of O-MWNTs. The molar ratio of EDC to O-MWNTs is 1:1. The amount of NHS added is about half of that of EDC. An appropriate amount of dehydrating agent, potassium carbonate, is added to promote the reaction. The reaction is carried out at room temperature for 2 hours. After the reaction is completed, the product is washed several times with deionized water and an organic solvent, ethanol or acetone, to remove unreacted impurities such as DCH, EDC, and NHS. After washing, it is dried in a vacuum or oven to obtain O-MWNTs grafted with DCH. The first transmission adhesion film layer 41 is Si3Al4O4 grafted with O-MWNTs of DCH x N4 film layer, on the basis of glass substrate 3, Ar and N2 (50:50 SCCM) were filled into the coating chamber, and the sputtering pressure was adjusted to 4*10 -1 Pa, the sputtering source is a SiAl target containing O-MWNTs grafted with DCH, Si:Al (92:8, calculated by mass percentage), the sputtering power is 250W, and the first transmission adhesion film layer 41 with a film thickness of 30nm is formed; on the basis of the first transmission adhesion film layer 41, Ar (30SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 4*10 -1 Pa, the sputtering source is NiCr target, the sputtering power is 20W, and the first transmission barrier layer 42 with a film thickness of 3nm is formed. The preparation of the first transmission layer 4 is completed.
[0103] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0104] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 7 is 52.5%, and the heat transfer coefficient is 0.35 W / (m 2 ·K).
[0105] Example 8 The difference between Example 8 and Example 7 is that DCH is first successfully grafted onto O-MWNTs by a chemical method, and then the modified O-MWNTs are dispersed in a solvent such as ethanol or isopropanol to form a stable dispersion. x In the process of N4 film layer, spin coating can be used to deposit Si3Al x N4 film before and after, the solution containing DCH grafted O-MWNTs was coated on the pretreated Si3Al x On the N4 film, the solution is spread evenly by high-speed rotation and then dried, leaving a layer of evenly distributed nanotube network, making it part of the film structure.
[0106] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0107] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 8 is 52.5%, and the heat transfer coefficient is 0.35 W / (m 2 ·K).
[0108] Example 9 The difference between Example 9 and Example 1 is that the second transmissive adhesion film layer 62 is Si3Al x N4 film or Si3Al doped with AZO and ZrO2 x N4 film, Si3Al containing AZO and ZrO2 x N4 film layer, film thickness 50-80nm. Ar and N2 (30-50:30-50 SCCM) are filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is a mixed target containing AZO target, ZrO2 target, and SiAl target, Si:Al (92-95:8-5, calculated by mass percentage), AZO: ZrO2: Si3Al x The ratio of N4 is 1:1:2, the sputtering power is 150-300W, and the sputtering time is adjusted to make the film thickness 70nm.
[0109] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0110] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 9 is 53.5%, and the heat transfer coefficient is 0.35 W / (m 2 ·K).
[0111] Example 10 The difference between Example 10 and Example 1 is that the second transmission barrier layer 61 is a NiCrAl film layer with a thickness of 5 nm. The thickness of the NiCrAl film layer is 3-5 nm. Ar (30-50 SCCM) is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is NiCrAl target, Ni:Cr:Al (50:30:20 calculated by mass percentage), the sputtering power is 10-20W, and the sputtering time is adjusted to make the film thickness 5nm.
[0112] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0113] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 10 is 50.5%, and the heat transfer coefficient is 0.34 W / (m 2 ·K).
[0114] Embodiment 11 The difference between Example 11 and Example 10 is that the first transmission barrier layer is a NiCrAl film layer, and its thickness is 5 nm.
[0115] When the liquid crystal dimming film 71 is powered off, the glass transmittance can be adjusted to 0% and the heat transfer coefficient to 0.32W / (m 2 ·K).
[0116] When a voltage of 70 V is applied to the liquid crystal dimming film, the light transmittance of Example 11 is 45.5%, and the heat transfer coefficient is 0.33 W / (m 2 ·K).
[0117] According to Examples 1 to 6, compared with Example 1, Example 2 has a first transmission adhesion film layer that helps more light penetrate, helps the visible light reflection color to present a neutral color, the first transmission barrier layer and the second transmission barrier layer are thinner, avoiding the problem of severe film absorption and a sharp drop in transmittance, the thickness of the connecting layer is thinner, and the thickness of the silica aerogel layer is thinner, which can reduce the influence of the connecting layer and the silica aerogel layer on the transmittance.
[0118] Compared with Example 2, Example 3 has a thinner second transmission adhesion film layer, so that more light is transmitted, and the infrared reflection layer is thinner, so less infrared light is reflected, and the thickness of the hollow cavity is thinner, resulting in an increase in the heat transfer coefficient.
[0119] Compared with Example 1, the photovoltaic components of Example 4 adopt a matrix-type spacing arrangement, which leads to a slight increase in light transmittance. However, the photovoltaic components adopt an overlapping layout, which can effectively increase the light receiving area and improve the overall power gain without sacrificing too much light transmittance.
[0120] Compared with Example 1, the thickness of the silica aerogel layer in Example 5 is too large, which can reduce the heat transfer coefficient while affecting the overall light transmittance. Compared with Example 1, the connecting layer in Example 6 has a heat insulation effect and can slightly reduce the heat transfer coefficient, but its thickness is too large and the light transmittance is lower than that of the modified EVA, which affects the overall light transmittance.
[0121] Although the conductive effect of Examples 7 and 8 is improved, the thin film layer does not affect the increase of the heat transfer coefficient. However, Examples 7 and 8 can reduce the charge accumulation on the surface of the glass substrate and reduce the adhesion of dust and foreign matter to affect the transmittance.
[0122] Example 9 Compared with Example 1, Si3Al doped with AZO and ZrO2 x The N4 film has higher transmittance and better thermal stability.
[0123] Compared with Example 1, the transmittance of the NiCrAl film layer in Example 10 is lower than that of the NiCr film layer, and the thermal insulation performance is better.
[0124] Compared with Example 10, Example 11 has two layers of NiCrAl film layers, which further reduce the transmittance and improve the thermal insulation performance accordingly.
[0125] The hollow layer of the present invention has the functions of sound insulation, heat insulation, anti-condensation and energy consumption reduction. The photovoltaic module is used to power the liquid crystal dimming film, which can realize the self-power supply of the liquid crystal dimming film. At the same time, the directional arrangement of the liquid crystal dimming film can actively adjust the visible light transmittance of the glass, and cooperate with the coated glass to realize the combination of active and passive, and two-way energy saving.
[0126] The preparation method of the present invention is stable and controllable, with a high yield rate. The self-powered dimming energy-saving insulating glass prepared can achieve a visible light transmittance of 0-60% through multi-adjustment, and the heat transfer coefficient can be reduced to 0.3-0.5 W / (m 2 ·K); The self-powered dimming energy-saving insulating glass prepared by the present invention can be widely used in the fields of construction and home furnishing, providing people with a more comfortable and healthy living environment.
[0127] The above examples are only used to further illustrate the technical content of the present invention, so that readers can understand it more easily, but they do not mean that the implementation of the present invention is limited to this. Any technical extension or re-creation made according to the present invention is protected by the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A dynamically adjustable coated glass, comprising coated glass (1) and a hollow layer (2), characterized in that: The coated glass (1) is provided with a glass substrate (3), a first transmission layer (4), an infrared reflection layer (5), and a second transmission layer (6) in sequence on the side facing the hollow layer (2); the hollow layer (2) is provided with a dimming layer (7) on the side facing away from the glass substrate (3); the dimming layer (7) is provided with a self-powered dimming glass system, and the self-powered dimming glass system comprises a liquid crystal dimming film (71) and a photovoltaic module (72); The first transmission layer (4) comprises a first transmission adhesion film layer (41) connected to the glass substrate (3), and a first transmission barrier layer (42) respectively connected to the first transmission adhesion film layer (41) and the infrared reflection layer (5); the second transmission layer (6) comprises a second transmission adhesion film layer (62) connected to the hollow layer (2), and a second transmission barrier layer (61) respectively connected to the second transmission adhesion film layer (62) and the infrared reflection layer (5); The dimming layer (7) comprises a first glass (73) located between the hollow layer (2) and the photovoltaic module (72), a second glass (74) located on a side of the liquid crystal dimming film (71) away from the photovoltaic module (72), and a connecting layer, wherein the connecting layer comprises a first connecting layer (701) arranged between the first glass (73) and the photovoltaic module (72), a second connecting layer (702) arranged between the liquid crystal dimming film (71) and the photovoltaic module (72), and a third connecting layer (703) arranged between the second glass (74) and the liquid crystal dimming film (71).
2. The dynamically adjustable coated glass according to claim 1, characterized in that: The first transmission adhesion film layer (41) is Si3Al x Si3Al2O3 films of N4 films or O-MWNTs grafted with 2-dimethylaminoethyl chloride hydrochloride x N4 film layer; the thickness of the first transmission adhesion film layer (41) is 30-50nm; the second transmission adhesion film layer (62) is Si3Al x N4 film or Si3Al doped with AZO and ZrO2 x N4 film layer, the thickness of the second transmission adhesion film layer (62) is 50-80 nm.
3. The dynamically adjustable coated glass according to claim 2, characterized in that: The first transmission barrier layer (42) is a NiCr film layer with a thickness of 3-5 nm, and the second transmission barrier layer (61) is a NiCr film layer or a NiCrAl film layer with a thickness of 3-5 nm.
4. The dynamically adjustable coated glass according to claim 2, characterized in that: The infrared reflection layer (5) is an AgPdAu alloy film layer, and its thickness is 10-20 nm.
5. The dynamically adjustable coated glass according to claim 1, characterized in that: The hollow layer (2) is provided with a hollow cavity (20) located between the coated glass (1) and the first glass (73), and a silica aerogel layer (21) located in the hollow cavity (20); the periphery of the hollow cavity (20) is sealed by a silicone structural adhesive; and the thickness of the silica aerogel layer (21) is between 1 and 5 mm.
6. The dynamically adjustable coated glass according to claim 1, characterized in that: The connecting layer is one of a modified EVA film or a PVB film, and has a thickness of 0.76-2.24 mm.
7. The dynamically adjustable coated glass according to claim 5, characterized in that: It also includes an aluminum frame (8) for sealing the coated glass (1) and the first glass (73); the aluminum frame (8) is connected to the coated glass (1) and the first glass (73) via butyl rubber; the hollow cavity (20) is located on the aluminum frame (8); and the thickness of the hollow cavity (20) is 9-22 mm.
8. The dynamically adjustable coated glass according to claim 1, characterized in that: The photovoltaic components (72) are arranged in an overlapping layout, and the photovoltaic components (72) are photovoltaic cells.
9. A method for preparing dynamically regulated coated glass, characterized in that: The dynamically adjustable coated glass according to any one of claims 1 to 8 comprises the following steps: S1, performing a tempering treatment on the glass substrate (3), cleaning it with deionized water in a glass cleaning machine, and then sending it into a pre-pumped magnetron sputtering coating machine to perform plasma bombardment on the cleaned glass substrate (3); S2, preparing the first transmission layer (4), on the basis of the glass substrate (3), filling Ar and N2 into the coating chamber, and adjusting the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is a SiAl target or a SiAl target containing O-MWNTs grafted with 2-dimethylaminoethyl chloride hydrochloride, the sputtering power is 150-300W, and a first transmission adhesion film layer (41) with a film thickness of 30-50nm is formed; on the basis of the first transmission adhesion film layer (41), Ar is filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is a NiCr target, the sputtering power is 10-20W, and a first transmission barrier layer (42) with a film thickness of 3-5nm is formed. The first transmission layer (4) is prepared; S3, preparing an infrared reflection layer (5), on the basis of the first transmission layer (4), filling Ar in the coating chamber, adjusting the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is AgPdAu target, the sputtering power is 150-300W, and the infrared reflection layer (5) with a film thickness of 30-50nm is formed. The infrared reflection layer (5) is prepared; S4, preparing the second transmission layer (6), on the basis of the infrared reflection layer (5), filling the coating chamber with Ar, and adjusting the sputtering pressure to 2-4*10 -1 Pa, the sputtering source is a NiCr target or a NiCrAl target, the sputtering power is 10-20W, and a second transmission barrier layer (61) with a film thickness of 3-5nm is formed; on the basis of the second transmission barrier layer (61), Ar and N2 are filled into the coating chamber, and the sputtering pressure is adjusted to 2-4*10 -1 Pa, the sputtering source is a SiAl target or a mixed target containing an AZO target, a ZrO2 target, and a SiAl target, the sputtering power is 150-300W, and a second transmission adhesion film layer (62) with a film thickness of 50-80nm is formed; the second transmission layer (6) is prepared; S5, preparing a dimming layer (7), connecting the liquid crystal dimming film (71) and the photovoltaic module (72) through a connecting layer, forming a self-powered dimming glass system through a circuit, and then using the connecting layer to connect the first glass (73) and the photovoltaic module (72), and the liquid crystal dimming film (71) and the second glass (74) respectively; S6, preparing a hollow layer (2), and sealing the coated glass (1) and the first glass (73) with an aluminum frame (8) by using butyl adhesive to form a hollow cavity (20), and filling the hollow cavity (20) with silica aerogel to form a silica aerogel layer (21); and sealing the surrounding side of the hollow cavity (20) with silicone structural adhesive, and the preparation of the self-powered dimming energy-saving hollow glass is completed.
10. A method for testing dynamically adjusted coated glass, characterized in that: The coated glass prepared by the method for preparing the dynamically adjusted coated glass according to claim 9 has the following measurement method: A. Preheat the machine; B. Measurement of glass power-off state; C. In the case of step B, perform visible light transmittance calibration; visible light transmittance measurement; D. In the case of step B, perform visible light reflectance calibration: measure the visible light reflectance of one side; measure the visible light reflectance of the other side; E. When the glass is powered off, calculate the heat transfer coefficient according to steps C and D; F. Measurement of glass power-on status; G. In the case of step F, performing visible light transmittance calibration; visible light transmittance measurement; H. In the case of step F, perform visible light reflectance calibration: measure the visible light reflectance of one side; measure the visible light reflectance of the other side; I. When the glass is powered on, calculate the heat transfer coefficient according to steps G and H.